Chip Formation When Drilling AISI 316L Stainless Steel using Carbide Twist Drill - Sultan, A.; Sharif, S.; Kurniawan, Denni (2015)
© 2015 The Authors Knowledge on the chip formation mechanism during drilling is very important to deliver the chips with size and shape as expected. Long chips cannot rid smoothly over drill flutes hence should be avoided while small chips can be removed easily from the machined hole. In this study, performance of a solid carbide twist drill through drilling of AISI 316L stainless steels was evaluated in terms of chip formation. This study aims to better define and further characterize the different chips shape and dimensions as a function of tool wear and cutting conditions in drilling the stainless steel. Experiments conducted on various combinations of cutting speed (18 and 30 m min-1) and feed rate (0.03, 0.045 and 0.06 mm rev-1) to present the differences in chip formation. Optical observation and comparative analysis of flank wear of the twist drill were done. As the results of the performed experiments, the lowest cutting speed-lowest feed rate reveals better performance due to desirable chips formation on austenitic stainless steels drilling.